Direct CP, Lepton Flavor, and Isospin Asymmetries in the Decays B -> K((*))l(+)l(-) - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2009)
We measure branching fractions and integrated rate asymmetries for the rare decays B→K(*)l+l-, where l+l- is either e+e- or μ+μ-, using a sample of 384×106 BB̄ events collected with the BABAR detector at the PEP-II e+e- collider. We find no evidence for direct CP or lepton-flavor asymmetries. However, for dilepton masses below the J/ψ resonance, we find evidence for unexpectedly large isospin asymmetries in both B→Kl+l- and B→K*l+l- which differ, respectively, by 3.2σ and 2.7σ, including systematic uncertainties, from the standard model expectations. © 2009 The American Physical Society.